Macrozoobenthic community assemblage as key indicator for mangrove restoration success in North Sumatra and Aceh, Indonesia. Issue 7 (3rd January 2022) - Basyuni, Mohammad; Bimantara, Yuntha; Cuc, Nguyen T. K.; Balke, Thorsten; Vovides, Alejandra G.
Abstract : The recognition of the high value of mangrove forests and the wide array of ecosystem services they provide has motivated investment in worldwide restoration efforts. However, current metrics of functional restoration (other than seedling survival rates and plant community composition) are often not readily available for local community managers, highlighting an urgency to identify easy‐to‐measure indicators to assess the functionality of restored mangroves. The macrozoobenthic community could be such practical indicator, as macrozoobenthic communities are sensitive to changes in their environment, and can be easily surveyed within local managing programs. Focusing on three main mangrove management conditions (natural, planted, and naturally regenerated) in North Sumatra and the province of Aceh, Indonesia, we compared vegetation and macrozoobenthic community diversity indices and identified environmental variables that best describe the forest management conditions and their associated macrozoobenthic community assemblage. Results showed that community assemblage, rather than macrozoobenthic diversity index, was associated with management conditions. The highest dissimilarity in macrozoobenthic community assemblages occurred between planted versus natural mangroves, with nonsignificant dissimilarity between natural and naturally regenerated mangroves. The Lined Nerite gastropod ( Nerita balteata ) was identified as an indicator of natural mangroves, and the invasive Giant African snail ( Achatina fulica ) was abundant in mangrove plantations, but also in natural mangroves bordering harbors, oil palm plantations, and aquaculture ponds, suggesting associated anthropogenic pressures. This study showed that the macrozoobenthic community can be used as restoration indicator and could serve as a baseline to empower monitoring activities and community‐based adaptive management practices to improve the outcomes of restoration efforts.